New Plants for Florida: Citrus - Fred Gmitter; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
The FAES team of citrus scientists has been recognized by the Florida citrus industry as an invaluable resource. In an integrated project funded by the industry, the labs are working together to address the most serious threats to the citrus industry. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.